Tafsir Atas Budaya Khatm Al-Qur’ān Di Pondok Pesantren Sunan Pandanaran Yogyakarta - Tinggal Purwanto (ILMU USHULUDDIN, 2020)
This article reveals the phenomenon of Khatm Al-Qur’ān culture in Pondok Pesantren Sunan Pandanaran (PPSPA) Yogyakarta. The author examines how Al-Qur’an’s Khatm culture is in PPSPA, what are the variations, as well as how the usage of Al-Qur’an’s Khatm by the PPSPA community. This article is to find that Al-Qur’an Khatm is not only a complete activity to read al-Qur’an by the Muslim community.  Khatm Al-Qur’ān in its development is done with various varians and different purposes so it is interesting to be examined more deeply. With the perspective of cultural interpretation, the use and understanding of the Muslim community towards the Qur’an Khatm is varied. This diversity looks at the cultural behavior of its community can be interpreted with its various dimensions: spiritual dimension, individual dimension, and social dimension.